Ethics in health services and policy a global approach - Harris, Dean M., 1951- (J-B public health/health services text ;, 2011)
"With this book nursing and health administration students can increase their understanding of the myriad global ethical issues. The book examines key issues of health services delivery (insurance, rationing of care, allocation of resources, and cost-containment) and the health care industry (corruption, kickbacks, and conflicts of interest) in both developing and developed countries. The book also considers cross-border issues that arise from the movement of patients and providers across national boundaries, such as treatment of undocumented aliens, medical tourism, and the "brain drain" of health care personnel from developing countries"--